A new approach for differentiability of interval-valued functions as first step toward fuzzy differentiability - Da Costa, Tiago M.; Lodwick, Weldon A.; Chaco-Cano, Y.; Silva, G. N. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
This manuscript presents a new approach to work with concepts of interval calculus, such as interval differentiability. Moreover, we present the relationship that there exists between our approach to interval differentiability and other interval differentiability concepts known in the literature. We consider that this is a first step toward a new way of formulating fuzzy differentiability.
Keywords: Context; Differential equations; Electronic mail; Periodic structures; Welding